Modernisation of historic housing complexe in Pyskowice = Modernizacja historycznych zespołów mieszkaniowych w Pyskowicach - Tomanek, Michał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In an Upper Silesian town Pyskowice, there are three urban complexes: a historic center with traditionally arranged medieval buildings, a housing complex built before World War II for the needs of railway workers and a housing estate built in connection with a planned vast industrial investment for its workers in the socialist realism times.
Keywords: kompleks miejski; zespół mieszkaniowy; centrum historyczne; Pyskowice; urban complex; historical center; emloyee housing